2007
DOI: 10.3201/eid1301.060716
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistantAcinetobacterInfection Mortality Rate and Length of Hospitalization

Abstract: Acinetobacter infections have increased and gained attention because of the organism’s prolonged environmental survival and propensity to develop antimicrobial drug resistance. The effect of multidrug-resistant (MDR) Acinetobacter infection on clinical outcomes has not been reported. A retrospective, matched cohort investigation was performed at 2 Baltimore hospitals to examine outcomes of patients with MDR Acinetobacter infection compared with patients with susceptible Acinetobacter infections and patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
288
2
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(324 citation statements)
references
References 34 publications
20
288
2
14
Order By: Relevance
“…Higher proportions of MDR in A. baumannii isolates among patients in ICUs were also found in other studies and can be explained by a more frequent use of invasive procedures like catheterisation or mechanical ventilation, a more common use of antibiotics and a higher proportion of critically ill patients compared to other ward types [12].…”
Section: Discussionsupporting
confidence: 77%
“…Higher proportions of MDR in A. baumannii isolates among patients in ICUs were also found in other studies and can be explained by a more frequent use of invasive procedures like catheterisation or mechanical ventilation, a more common use of antibiotics and a higher proportion of critically ill patients compared to other ward types [12].…”
Section: Discussionsupporting
confidence: 77%
“…A high colistin resistance rate of 30.6% among A. baumannii isolates from 2 Korean hospitals (Ko et al, 2007) indicated necessity of colistin susceptibility testing in other settings. With a recent increase of multiresistant Acinetobacter isolates in many countries, selection of appropriate antimicrobial agents has become very difficult, resulting in increased patient mortality (Munoz-Price and Weinstein, 2008;Sunenshine et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are now mounting data to suggest that the presence of Acinetobacter can contribute adversely to the prognosis of patients, especially in the presence of significant comorbidities (Grupper et al, 2007;Murray & Hospenthal, 2008), and multidrug resistance in such isolates is associated with increased mortality and prolonged hospitalization (Lee et al, 2007;Sunenshine et al, 2007). Furthermore, since carbapenems are frequently used for the treatment of such multidrug-resistant Acinetobacter infections, carbapenem resistance can further contribute to mortality as a result of discordant empirical therapy (Kwon et al, 2007).…”
Section: Clinical and Epidemiological Datamentioning
confidence: 99%
“…have become major pathogens in hospital-associated infections, especially in critical care settings such as intensive care units (ICUs) and units for patients with severe burns (Murray & Hospenthal, 2008;Sunenshine et al, 2007). They can survive in the hospital environment for long periods and have a remarkable propensity to develop resistance to multiple classes of antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%